Relevance of anaesthesia type on early neurological outcome in acute ischemic stroke patients undergoing mechanical thrombectomy - Šalaševičius , L.; Vilionskis , A. (Neurologijos seminarai, 2018)
Background. Conscious sedation (CS) and general anaesthesia (GA) are types of anaesthesia used during mechanical thrombectomy (MTE). Currently, there are no guidelines on which type of anaesthesia to choose during MTE. Retrospective studies suggest that GA is associated with worse clinical outcomes, while latest clinical studies show no such difference.Materials and methods. Acute stroke patients treated in two Vilnius hospitals and undergoing MTE were included. Patients were divided into two groups according to the type of anaesthesia: general anaesthesia (GA) and conscious sedation (CS). Demographic, clinical and logistic data were evaluated. Primary end point was good outcome 24 hrs after MTE. Safety of the procedure (7-day mortality and symptomatic intracerebral haemorrhage (sICH)) was also evaluated.Results. 248 patients were included in the analysis. 105 patients (42.3%) received GA and 143 (57.7%) – CS. Baseline data was similar in both groups, except for atrial fibrillation (55.9% in CS vs 37.1% in GA, p=0.003) and bridging therapy (66.4% in CS vs 46.7% in GA group, p=0.003). Good outcome 24 hrs after MTE was achieved in 51.4% (n=54) patients in GA group and 58.7% (n=84) patients in CS group (p=0.252).There was no difference in 7-day mortality and sICH between the study groups. Periprocedural arterial blood pressure levels were significantly lower in GA group (p
Keywords: mechanical thrombectomy; ischemic stroke; anaesthesia; general anaesthesia; conscious sedation